Cerebral Regional Homogeneity Alternation of Pregnant Women With Antenatal Depression During the Pandemic - Cheng, Bochao; Meng, Yajing; Zhou, Yushan; Li, Jinrong; Zeng, Jianguang; Tan, Xi; Zhang, Kaiyou; Luo, Ya; Zhang, Yan (Frontiers in Psychiatry, 2021)
Objective: The Coronavirus Disease 2019 (COVID-19) pandemic emerged in Wuhan, China. Ranges of precaution in China kept large number of people in isolation, which push the huge stress to the pregnant woman and trigger the antenatal depression (ATDP). This research aims to explore neurobiological mechanisms underlying ATDP, which impedes early detection and intervention for this disorder. Methods: A total of 43 singleton pregnant women were recruited, including 21 treatment-naïve ATDP patients and 22 healthy pregnant women (HPW). To explore the intrinsic cerebral activity alternations in ATDP using resting-state functional MRI (rsfMRI). We investigated the local regional homogeneity (ReHo) differences in two groups using the voxel-based whole-brain analysis. As well as the correlation between the regional functional abnormalities and clinical variables in ATDP patients was examined. Results: Compared with HPW, ATDP patients showed decreased ReHo in the left dorsolateral prefrontal cortex, right insular and the cluster coving right ventral temporal cortex (VTC), amygdala (AMG) and hippocamus (HIP). The Edinburgh Postnatal Depression Scale (EPDS) scores of ATDP patients negatively correlated with the ReHo in the right VTC, AMG and HIP. Conclusion: Elucidating the neurobiological features of ATDP patients undergo the threaten of COVID-19 is critical for developing adequate methods for early diagnosis, precautious and intervention.